PENGARUH PRESTASI KERJA DAN KOMPETENSI KARYAWAN TERHADAP PROMOSI JABATAN PADA PT AGUNG AUTOMALL TOYOTA BENGKULU - nadiyen, elsa; Meiffa Herfianti (Jurnal Ilmiah Akuntansi, Manajemen dan Ekonomi Islam (JAM-EKIS), 2024)
Work performance is the main key to a company's success in achieving its goals. A company needs employees who have the right work performance and employee competencies to achieve the desired promotion. This research aims to determine the influence of work performance and employee competency on position promotion at PT Agung Automall Toyota Bengkulu. This research uses quantitative methods and the object of this research is employees of PT Agung Automall Toyota Bengkulu, a sample of 130 respondents. The data collection technique uses a questionnaire. The analysis technique used is multiple linear regression. This research uses validity tests, reality tests, classical assumption tests followed by hypothesis testing. Based on the results of multiple linear regression analysis, the regression equation Y 2.036 0.463 (X1) + 0.713 (X2) is obtained. The research results and hypothesis show that Job Performance (sig α = 0.000 < 0.050), Employee Competence (sig α = 0.002 < 0.050). From the results of the hypothesis test, it shows that there is a simultaneous influence of Job Performance and Employee Competency on Job Promotion and shows that there is a significant influence of Job Performance and Employee Competency partially on Job Promotion.